Um percurso entre práticas artísticas na cidade de Fortaleza: diálogos entre arte, comunicação, cidade e tecnologia - Vasconcelos, Allan Diniz Ferreira (2017)
Starting from the idea of city as an amplified field for communication and art, this theoretical-pratical research aims to investigate artistic experimentations that involve the handling of new technologies, mobile devices and locative medias, establishing a direct relation with Fortaleza city. Based on a route passed through observation, participation, construction of relations and experience exchanges, it was made an analysis from the work of three artists that operate in Ceara's capital: David da Paz, Cecília Andrade and André Lopes. The approximation and diversity of these artistic proposals bring matters like assemblage of collaborative practises; dialogues between geo localized video performances and nomad poetics; erasures and dispute of urban imaginary; notions of public, private and virtual social medias on daily environments; neighbourhood, proximity and surroundings connected to the use of ordinary technologies; contributing to the construction of a thought that presents possible configuration dynamics of contemporary cybercities. Based upon notions of sitespecific and De Certeau's view about ways to invent and practise the daily life, critical outcomes are build from a social space connected by creative ways of being a part of a city tensioned by informative flow and intense political-economic-social transformation process.